Penyusunan Rencana Anggaran Pendapatan dan Belanja Koperasi (RAPBK): Pelatihan Perkoperasian bagi Pengelola Koperasi se Jawa Barat - Wahyudin, Wahyudin (E-Coops-Day, 2024)
One of the tasks of cooperative management is to prepare the Cooperative Budget and Expenditures (RAPBK) which is usually done at the Annual Member Meeting. Preparing this budget is important to know what the cooperative will implement in the future or next year. Preparing a budget requires several conditions so that the budget and realization do not deviate too much, namely the budget must be realistic and enforceable and based on valid data so that it is not taken carelessly in its preparation. By preparing the RAPBK, it will also be known when the cooperative will get a surplus of funds and when it will get a deficit. So that the shortage of funds could have been anticipated beforehand. and can anticipate what must be done to cover the funding shortfall.